Opini Audit, Nilai Aset, Dan Kemandirian Daerah Sebagai Determinan Audit Delay: Studi Empiris Pada Pemerintah Provinsi Di Indonesia 2018-2021 - Pambudi, Kukuh; Fachrudin, Fachrudin; Robin, Robin; Pratama Abdi Muhammad, Nur (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
Since 2003, Indonesia has gone through a financial reform. Based on Law No. 13/2004, the Audit Board of Indonesia (BPK) is required to submit the audit report (LHP) including the audit opinion to the Regional People’s Representative Council (DPRD) no later than 2 (two) months after the unaudited financial report is submitted by the local government. This becomes BPK's guideline in completing its audit to avoid delays. During 2017-2021, the audit opinion on local government financial reports (LKPD) has increased. This increase in opinion includes an increase in the unqualified opinion (WTP) to 92.4% of the 2021 financial statements from 76% in 2017. This study aims to answer research gaps related to the effect of audit opinion, local government size through asset value as a proxy, and local autonomy on audit delay. Furthermore, it is important to obtain empirical evidence about the effect of opinion, local government size, and local autonomy on audit delay.